Five-Year Period Prevalence and Characteristics of Anemia in a Large US Inflammatory Bowel Disease Cohort. Issue 8 (September 2016) - Koutroubakis, Ioannis E.; Ramos-Rivers, Claudia; Regueiro, Miguel; Koutroumpakis, Efstratios; Click, Benjamin; Schwartz, Marc; Swoger, Jason; Baidoo, Leonard; Hashash, Jana G.; Barrie, Arthur; Dunn, Michael A.; Binion, David G.
Abstract : Background: Anemia is a common manifestation of inflammatory bowel disease (IBD), but its prevalence in the United States is not well defined. Aim of this study was to determine the prevalence and characteristics of anemia in IBD patients who were followed in a US referral center. Materials and Methods: Demographic, clinical, laboratory, and treatment data from a prospective, consented longitudinal IBD registry between the years 2009 and 2013 were analyzed. Disease activity was evaluated using Harvey-Bradshaw index in Crohn's disease (CD) and ulcerative colitis (UC) activity index in UC as well as C-reactive protein and erythrocyte sedimentation rate. Anemia was defined based on the World Health Organization criteria. Results: A total of 1821 IBD patients (1077 with CD, 744 with UC, median age 43.8 y, 51.9% female) were included. The 5-year period prevalence of anemia in IBD patients was 50.1%, (CD: 53.3% vs. UC: 44.7%, P =0.001). In multivariate logistic regression analysis, anemia was associated with surgery for IBD [odds ratio (OR)=2.77; 95% confidence interval (CI), 2.21-3.48; P <0.0001], female gender (OR=1.29; 95% CI, 1.04-1.61; P =0.02), C-reactive protein (OR=1.26; 95% CI, 1.16-1.37; P <0.0001), erythrocyte sedimentation rate (OR=1.02; 95% CI, 1.01-1.03; P =0.0002), and use of biologics (OR=2.00; 95% CI, 1.58-2.52; P =0.0001) or immunomodulators (OR=1.51; 95% CI, 1.21-1.87; P =0.0003). Iron replacement therapy was administered to 46.8% of the anemic patients. Conclusion: Anemia has a high period prevalence in IBD patients followed at a tertiary center. Anemia is more common in CD than in UC, is associated with disease activity, and in current practice is undertreated.